Failure analysis around oriented boreholes using an analytical model in different faulting stress regimes - Lakirouhani, Ali; Ghorbannezhad, Sahar; Medzvieckas, Jurgis; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2023)
One of the most important instabilities that may occur in a borehole is shear instability caused by high compressive stress in the borehole wall. The initial estimation of the width and depth of the failure zone around the borehole is very important in the field. In inclined boreholes, the shear instability or borehole breakout is affected by the in situ stress regime, the deviation angle of the borehole, the mechanical properties of the rock and the effect of the intermediate principal stress. In this article, an analytical model based on theory of elasticity is presented to find the breakout failure area around the inclined boreholes. Mogi-Coulomb shear failure criterion is used, in which there is also the effect of the intermediate principal stress. This model examines the failure in three-dimensional elements around the borehole for different in situ stress regime. The main finding of the analysis done in this article is that not only the deviation angle of the borehole but also the in situ stress regime has a great effect on the dimensions of the breakout. Also, the plane where the deviation angle of the borehole changes, affects the dimensions of the breakout.